Integrated Microbiome and Host Transcriptome Profiles Link Parkinson’s Disease to Blautia Genus: Evidence From Feces, Blood, and Brain - Guo, Xingzhi; Tang, Peng; Hou, Chen; Chong, Li; Zhang, Xin; Liu, Peng; Chen, Li; Liu, Yue; Zhang, Lina; Li, Rui (Frontiers in Microbiology, 2022)
A link between the gut microbiome and Parkinson’s disease (PD) has been intensively studied, and more than 100 differential genera were identified across the studies. However, the predominant genera contributing to PD remain poorly understood. Inspired by recent advances showing microbiota distribution in blood and brain, we here comprehensively investigated currently available fecal microbiome data (1914 samples) to identify significantly altered genera, which were further validated by comparison to the results from microbiome analysis of blood (85 samples) and brain (268 samples). Our data showed that the composition of fecal microbiota was different from that of blood and brain. We found that Blautia was the unique genus consistently depleted across feces, blood, and brain samples of PD patients (P < 0.05), despite using rigorous criteria to remove contaminants. Moreover, enrichment analyses revealed that host genes correlated with Blautia genus abundance were mainly involved in mitochondrial function and energy metabolism, and mapped to neurodegenerative diseases (NDDs) and metabolic diseases. A random forest classifier constructed with fecal microbiota data demonstrated that Blautia genus was an important feature contributing to discriminating PD patients from controls (ROC-AUC=0.704, PRC-AUC=0.787). Through the integration of microbiome and transcriptome, our study depicted microbial profiles in the feces, blood, and brain of PD patients, and identified Blautia genus as a potential genus linked to PD. Further studies are greatly encouraged to determine the role of Blautia genus in the pathogenesis of PD.